2017
DOI: 10.2147/por.s118648
|View full text |Cite
|
Sign up to set email alerts
|

Impact of primary care exercise referral schemes on the health of patients with obesity

Abstract: Primary care exercise referral schemes (ERSs) are a potentially useful setting to promote physical activity (PA). It is not established, however, whether interventions to increase PA, such as ERSs, have differing health outcomes according to the participants’ body mass index (BMI). This paper summarizes evidence for the impact of primary care ERSs on the health of people with obesity and reports findings of a reanalysis of the EMPOWER study, providing the first data to report differential outcomes of ERSs by B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
0
5
1
Order By: Relevance
“…Exercise referral is not intended as a weight loss programme per se [ 5 ], yet our study found that participants did experience weight loss. Our findings are favourable compared to little or no weight loss reported for general referrals across a number of other ERS [ 9 , 22 ]. In total, 1061 participants completed the ERS and reported some level of increased PA, indicating that that the scheme is to a large extent successful in its intended outcome (PA change) for those who adhere.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Exercise referral is not intended as a weight loss programme per se [ 5 ], yet our study found that participants did experience weight loss. Our findings are favourable compared to little or no weight loss reported for general referrals across a number of other ERS [ 9 , 22 ]. In total, 1061 participants completed the ERS and reported some level of increased PA, indicating that that the scheme is to a large extent successful in its intended outcome (PA change) for those who adhere.…”
Section: Discussioncontrasting
confidence: 52%
“…Notwithstanding this issue, the impact on ERS effectiveness for other referral conditions has been examined previously with some success indicated for cardiovascular and mental health referrals [ 17 ]. For weight-related referrals, the evidence is scarce, however, and the true impact of referring patients with elevated weight to ERS needs to be understood, in terms of both PA and weight change, and engagement and retention [ 12 , 18 , 19 , 20 , 21 , 22 ]. What is clear is that ERS does not work for all; “success” can be influenced by socioeconomic and demographic factors, and participant relationships with ERS can be problematic and heavily influenced by complex life circumstance [ 21 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Length of schemes, and mode and type of exercise used with each sub-group, was reviewed due to inconsistencies in previous research [ 2 ]. At present, strong research is lacking to support ERS of 12-week duration which are recommended by NICE [ 22 ], particularly with respect to adherence to PA prescribed; evidence suggests schemes do not tailor the mode and type of exercise specifically to suit health disorders; and the evidence to support ERS in specific disorders in relation to adherence and improving health outcomes is poor [ 2 , 25 , 28 ]. These two key variables will be discussed further in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the success of ERS is highly swayed by uptake to schemes and adherence [ 27 ]. Important evidence of the efficacy of ERS has been generated [ 2 , 21 , 26 , 28 ], although effectiveness is influenced by the quantity of referrals who participate until completion.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Previous attempts to reduce physical inactivity have focussed on individualistic approaches, such as exercise referral/on prescription programs, clinical populations and community groups and whilst some have shown improvement for specific population groups, they have made little impact at community-wide level. [7][8][9][10][11] In 2017, Schiphorst et al, identified the seven best investments to increase population physical activity levels. These included, 1) Communication and public education, 2) Transport and the environment, 3) Urban design and infrastructure, 4) Healthcare and health education, 5) Education, 6) Community-wide programs, and 7) Sport and recreation.…”
Section: Introductionmentioning
confidence: 99%